Integration of Cangkal Cultural Values in Financial Literacy Education: Its Impact on Financial Attitudes, Knowledge, and Skills of Junior High School Students - Raihanah Sari; Sutarto Hadi; Ananda Setiawan; Herry Porda Nugroho Putro; Ersis Warmansyah Abbas; Rochgiyanti (Universitas Muhammadiyah Surakarta, 2025)
Financial literacy among students is at 23.4% and is categorized as low. This has led to increasingly high levels of consumerism and even stress. The Banjar community has a work culture known as cangkal. Cangkal refers to a persistent and diligent work ethic. Financial literacy education has an impact on students' attitudes, knowledge, and financial skills. This study aims to analyze the influence of integrating the cultural values of cangkal into financial literacy education on attitudes, knowledge, and skills. This is a quantitative study using Structural Equation Modeling-Partial Least Squares (SEM-PLS). This study was conducted in the city of Banjarmasin and Barito Kuala Regency, involving seven junior high schools with a sample size of 422 respondents from grade VII. The findings of this study are: (1) Cangkal culture has cultural values such as trust, hard work, and preference; (2) The integration of Cangkal cultural values in financial literacy education has a positive influence on attitudes, knowledge, and skills. This can be seen from the path coefficient values that are close to +1, indicating a positive and increasingly strong relationship between these variables, with results of 0.932 for knowledge, 0.921 for attitude, and 0.909 for financial skills. The conclusion of this study is that the integration of Cangkal cultural values into financial literacy has a positive influence on financial knowledge, financial attitudes, and financial skills. Further research with a different focus is expected to strengthen this study.